“Conservative” surgical treatment for anterior knee pain - Post, William R. (Annals of Joint, 2018)
This article provides a common sense, logical, biologically sound and minimally invasive surgical approach to treating specific recalcitrant causes of anterior knee pain (patellofemoral pain). Accurate diagnosis by careful history, physical examination and judicious imaging followed by focused surgical intervention and rehabilitation within the patient’s envelope of function can result in excellent patient outcomes in the majority of cases.